Gangguan Berbahasa pada Anak Autis Ringan : Studi Kasus Anak Usia 13 Tahun - Annisa Aulia Rahma; Akifah Humaira Salsabila (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Language disorders mean obstacles, obstacles, and something that causes a person's inability to pronounce articulation sounds, or words to express, say, and convey thoughts, ideas, and feelings. This study aims to describe language disorders in mild autistic children aged 13 years. This research was conducted using a descriptive qualitative method. The data in this study are the results of a 13-year-old conversation with a subject with mild autistic disorder with the initials "Y" and currently occupying a 5th grade school at the Special School in Lebak Bulus. The data in the study were collected using the engaged listening technique, recording technique, and note taking technique. Based on the results of the study, the subject has many language disorders which cause difficulty communicating, so that other people do not understand the language used, and the subject alternates phonemes so that the meaning of the words spoken are different from what should be said so that other people cannot understand.